2021
DOI: 10.1192/bjp.2021.132
|View full text |Cite
|
Sign up to set email alerts
|

Pre-pandemic mental health and disruptions to healthcare, economic and housing outcomes during the COVID-19 pandemic: evidence from 12 UK longitudinal studies

Abstract: Background The COVID-19 pandemic has disrupted lives and livelihoods, and people already experiencing mental ill health may have been especially vulnerable. Aims Quantify mental health inequalities in disruptions to healthcare, economic activity and housing. Method We examined data from 59 482 participants in 12 UK longitudinal studies with data collected before and during the COVID-19 pandemic. Within each study, we estimated the association between psychological distr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 27 publications
1
19
1
Order By: Relevance
“…For instance, a recent study [ 9 ] found that the risk of debt accumulation is greater among individuals who have previously suffered from mental health difficulties, while another [ 43 ] found that existing mental health difficulties at one time-point did not increase risk of debt at subsequent time points. Moreover, research has shown how those with poorer pre-pandemic mental health were more likely to encounter economic disruptions (i.e., usual economic activity, job loss, loss of income, changes to working hours) due to the pandemic [ 44 ]. Therefore, it may be that pre-existing mental health conditions prior to the pandemic coupled with the financial implications of the pandemic may have resulted in the substantial effect sizes observed in the association between perceptions of debt manageability on mental health outcomes in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a recent study [ 9 ] found that the risk of debt accumulation is greater among individuals who have previously suffered from mental health difficulties, while another [ 43 ] found that existing mental health difficulties at one time-point did not increase risk of debt at subsequent time points. Moreover, research has shown how those with poorer pre-pandemic mental health were more likely to encounter economic disruptions (i.e., usual economic activity, job loss, loss of income, changes to working hours) due to the pandemic [ 44 ]. Therefore, it may be that pre-existing mental health conditions prior to the pandemic coupled with the financial implications of the pandemic may have resulted in the substantial effect sizes observed in the association between perceptions of debt manageability on mental health outcomes in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The UK National Core Studies – Longitudinal Health and Wellbeing initiative aims to co-ordinate primary analyses across multiple UK longitudinal population-based studies. 13,14 Co-ordinating analyses across different datasets minimises methodological heterogeneity and maximises comparability, while appropriately accounting for the study design and characteristics of individual datasets.…”
Section: Methodsmentioning
confidence: 99%
“…There are therefore concerns that lockdown measures may have exacerbated these pre-existing inequalities in healthcare. 5,11 It is essential to investigate the performance of the healthcare system and assess its ability to manage non-COVID-19 health conditions during the pandemic. We envisage that such investigations will facilitate data-driven, evidence-based policy decisions to help mitigate adverse knock-on healthcare impacts of the pandemic and improve healthcare system resilience during any future pandemic or climaterelated stresses.…”
Section: Introductionmentioning
confidence: 99%